Prototype of traffic light control system - Hashim, Nik Mohd Zarifie (2014)
Traffic congestion became a common problem which contributed huge impact to the community in large and at the same time to the transportation system. A prototype of traffic light controller system is designed in order to resolve these problems. This prototype system was designed to be operated on radio frequency (RF) transmission and used the Programmable Integrated Circuit (PIC) 16F877A microcontroller to change the traffic light sequence when it was triggered by the remote control. This system will reduce accidents which often occur at the traffic light intersections because of other vehicle had to huddle for given a special route to emergency vehicle. As the result, this project successful analyzing and implementing the wireless communication; the radio frequency (RF) transmission in the traffic light control system for emergency vehicles. In future, this prototype system can be improved by controlling the real traffic situation e.g. in the main busy traffic light places and analyzed the effectiveness of the remote controller usage by considering the length of remote and the traffic light location.